When Celebrities Count: Power Distance Beliefs and Celebrity Endorsements - Winterich, Karen Page; Gangwar, Manish; Grewal, Rajdeep (Journal of Marketing, 2018)
The use of celebrity endorsements varies across countries; does their effectiveness similarly vary across cultures? The authors propose that power distance beliefs (PDB), a cultural orientation related to the extent to which people expect and accept differences in power, moderate the effects of celebrity endorsements. A positive effect of celebrity endorsers on evaluations of advertising should be more potent with greater PDB; source expertise and trustworthiness likely underlie this effect. To test the hypotheses, the authors use moderated mediation analyses, with corrections for measurement error and endogeneity of the mediators (source expertise and trustworthiness). The results of three studies, using both manipulated and measured PDB for respondents in different countries and with a variety of endorsers, demonstrate that PDB determine the effectiveness of celebrity endorsements on attitudes toward the advertisement and the brand. In support of the moderated mediation model, perceptions of source expertise and trust mediate the effect of celebrity endorsements, conditional on PDB. The results hold for nondurables but do not generalize to durable products.